2000
DOI: 10.1046/j.1463-5224.2000.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Lens‐induced uveitis

Abstract: has been described in humans and many animal species. Traumatic rupture of the lens capsule may result in vision-threatening intraocular inflammation that is poorly responsive to medical management. Phthisis bulbi, persistent uveitis or glaucoma often occurs in these eyes. Surgical removal of the lens material is generally indicated shortly after the injury in an effort to preserve vision. Leaking of lens proteins through an intact lens capsule may result in a lympho-plasmacytic anterior uveitis. This is most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 52 publications
4
44
0
7
Order By: Relevance
“…Notably, abnormally low IOPs, severe retinal defects and severely damaged optic nerves were usually observed in the same eyes, suggesting that the optic nerve degeneration in these mice is not simply IOP-related retinal ganglion cell death but may be a consequence of other defects. It has been shown that primary lens defects and leaked lens material into the anterior chamber can cause inflammation and ocular pathology including uveitis and phacolytic glaucoma (Ellant and Obstbaum, 1992; Wilcock and Peiffer, 1987; Van Der Woerdt, 2000; Flocks et al, 1955; Yan et al, 2014). However, we did not observe macrophages or other inflammatory debris in the anterior chambers or the drainage structures of MLR10 Cre ;Col4a1 Flex41/Flex41 mice by histology (…”
Section: Resultsmentioning
confidence: 99%
“…Notably, abnormally low IOPs, severe retinal defects and severely damaged optic nerves were usually observed in the same eyes, suggesting that the optic nerve degeneration in these mice is not simply IOP-related retinal ganglion cell death but may be a consequence of other defects. It has been shown that primary lens defects and leaked lens material into the anterior chamber can cause inflammation and ocular pathology including uveitis and phacolytic glaucoma (Ellant and Obstbaum, 1992; Wilcock and Peiffer, 1987; Van Der Woerdt, 2000; Flocks et al, 1955; Yan et al, 2014). However, we did not observe macrophages or other inflammatory debris in the anterior chambers or the drainage structures of MLR10 Cre ;Col4a1 Flex41/Flex41 mice by histology (…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, phacotoxic uveitis, an ocular inflammatory condition associated with hypermature cataract in animals, appears to be caused by the release of lens crystallins through intact lens capsules (Coulter et al, 1999; van der Woerdt, 2000). Quantitatively, the diffusion rates of intermediate size molecules in the lens capsule differ based on molecular size.…”
Section: Physical and Biomechanical Propertiesmentioning
confidence: 99%
“…Atualmente, as taxas de sucesso da cirurgia de facoemulsificação em cães situam-se em torno de 80% a 90%, diminuindo em cerca de 10% a 20% após três a cinco anos do ato cirúrgico . A facoemulsificação em cães portadores de uveíte induzida pela lente (uveítes facolíticas) apresenta uma redução nas taxas de sucesso para aproximadamente 52% (Dziezyc 1990, Whitley et al 1993, Van der Woerdt 2000, Leasure et al 2001. Em decorrência disso, diversos protocolos pré e pós-operatórios, que utilizam agentes anti-inflamatórios esteroidais e não esteroidais, têm sido empregados na tentativa de controle da uveíte cirurgicamente induzida (Williams et al 1996).…”
Section: Introductionunclassified